Studying the Attitudes-Behavior Gap in Ethical Consumerism: A review of Research - Nindria Untarini (Universitas Diponegoro, 2020)
The attitude of consumers who are pro-environment does not always lead to buying behavior on environmentally friendly products. Although consumers are regularly exposed to environmentally friendly product messages, this does not always have an impact on actual changes in behavior. To encourage understanding of consumer behavior of environmentally friendly products going forward, this paper aims to identify deeper the causes of attitude gaps - behavior and solutions to overcome them to obtain knowledge about integrated and holistic conceptual models related to consumer behavior gaps in the consumption of environmentally friendly products. This paper discusses the significant limitations in the consumption of environmentally friendly products and raises an understanding of consumer behavior of environmentally friendly products in the future. Furthermore, the operationalization of this model offers knowledge and strategic direction for marketing managers who seek to bridge the gap in consumer attitudes.